A formação do enfermeiro para atenção às urgências e emergências na Atenção Básica em Saúde - Vieira, Carla Roberta Sola de Paula (Universidade Federal de São Carlos, 2017)
There are few advances in research on the formation of the nurse practitioner for urgent and emergency assistance, on the epidemiological profile of the brazilian population. Networking puts Basic Health Attention with in strategic position as ordering, care. Assuming a definitive role in what relates to maintenance of the life of patients. The role of the nurse in this network, is cross because it permeates the whole route of this watch. The formation of nurses requires constant professional improvement, since this is a complex and integral action. Learning scenarios allow for greater contact with the reality of the environment in which they live, providing a horizon of paths to creativity and transformations. It is descriptive, exploratory study of qualitative approach, with the purpose of analyzing the formation of nurses in the Basic Health Attention. “in the light” of the public policy of attention to urgencies and emergencies in four graduate programs in nursing schools located in the State of São Paulo. Data analysis and discussion will occur under criteria of National curriculum guidelines were carried out through the realization of interviews semi-structured with coordinators of courses, teachers and those responsible for emergency and emergency education. As a result, we can identify that only two of the four universities have discipline specifies inurgent and emergency area, allowing for the planning and structuring of primary content to your professional practice. Universities that do not have the discipline of emergency and emergency condition theme approach to evaluation each faculty member about the importance of urgent and emergency education on graduation. Learn how urgent and emergency is a social need which reflects directly on the quality of services provided in the health system that learning is enhanced when you approach the teaching of different professions of the health area, promoting interdisciplinarity as daily practice and, thus, enhancing the care centered on the individual.
Keywords: Currículo; Educação em Enfermagem; Emergências; Curriculum; Education in Nursing; Emergencys; CIENCIAS DA SAUDE::ENFERMAGEM